The first case report of complement component 7 deficiency in Qatar and a 10-year follow-up - Khalil, Sally Mahgoub; Aqel, Sami; Mudawi, Dalal Sideeg; Mobayed, Hassan; Al-Nesf, Maryam Ali (Frontiers in Immunology, 2023)
Introduction: Neisseria meningitidis is a significant cause of bacterial meningitis and septicemia worldwide. Recurrent Neisseria meningitidis is frequently associated with terminal complement protein deficiency, including Complement component 7. This report discusses the first case of C7 deficiency in Qatar. Case Report: A 30-year-old Qatari man presented with a meningococcal infection, which was verified by a blood culture. He experienced two episodes of meningitis caused by an undetermined organism. His blood tests revealed low levels of CH50 and C7. His C7 gene testing revealed a homozygous mutation in exon 10 (c.1135G>C p.Gly379Arg), a mutation that has not been previously documented in Qatar. However, it has been observed in 1% of Moroccan-origin Israeli Jews who also exhibit C7 deficiency. Regular prophylactic quadrivalent vaccinations against types A, C, Y, and W-135 with azithromycin tabs were administered. Over the last 10 years of follow-up, he remained in good health, with no further meningitis episodes. Conclusion: To our knowledge, this is the first confirmed case of C7 deficiency reported in the Arabian Gulf countries. Such rare diseases should be a public health priority. Awareness among medical practitioners and the community should help with early detection of C7 deficiency and the prevention of its consequences.